Profiling and simultaneous quantitative determination of oligostilbenes in Paeonia ostii seed shell from different geographical areas in China and their comparative evaluation. Issue 4 (4th April 2019) - Zhang, Lina; Liu, Pu; Gao, Jiayu; Wang, Xinsheng; An, Jiamin; Xu, Shijing; Deng, Rui‐xue
Abstract: Introduction: The Paeonia ostii T. Hong & J. X. Zhang seed shell, characterised by a high content of oligostilbenes, is one of the two most important by‐products in the preparation of seed oil. Oligostilbenes are considered characteristic constituents of the genus Paeonia, and can be used in fingerprinting to determine the geographical origin and the quality of raw materials. Objective: To develop and optimise a simple and reproducible high‐performance liquid chromatography diode array detection (HPLC‐DAD) method for the simultaneous determination of seven oligostilbenes in P. ostii seed shell from different geographical areas, and to associate the cultivation area. Methodology: A validated HPLC method coupled with a DAD detector was performed for the detection and determination of target compounds in the samples. Optimal chromatographic conditions were achieved using an Agilent Zorbax Eclipse SB‐AQ‐C18 column and a gradient elution with acetonitrile and potassium dihydrogen phosphate solution. Results: The proposed quantitative method showed appropriate accuracy and precision, and was successfully applied to the routine analysis of seven oligostilbenes and the quality evaluation of 50 P. ostii seed shell samples. There were significant differences between the contents of the seven oligostilbenes in different samples ( P < 0.01). Conclusion: The results demonstrated that the oligostilbenes were main secondary metabolites in the P. ostii seed shells, and the content of seven components in P. ostii seed shells sourced from different cultivation areas in China was different. Abstract : The optimum resolution of seven oligostilbenes was achieved, and the influence of geographical difference on the main oligostilbenes contents of Paeonia ostii seed shell sourced from different cultivation areas in China was detected. The satisfactory results demonstrated that the oligostilbenes were main secondary metabolites in P. ostii seed shells, and content of the seven analytes in P. ostii seed shells from different samples sourced from different cultivation areas in China was different because of the difference of the growth environment cultivation conditions. The proposed method showed appropriate accuracy and precision, and was useful for the routine analysis of oligostilbenes and the quality evaluation for P. ostii seed shells owing to its simplicity.